Adding synesthetic metaphors in English-Ukrainian translations of fiction - Zhulavska, Olha; Kulish, Vladyslava; Chernyk, Maryna (Lesya Ukrainka Eastern European National University, 2024)
This article combines analytical tools of cognitive translation analysis and affordances of corpus linguistics to inquire into the translation procedure of adding synesthetic metaphoric descriptions in English-Ukrainian translations of fiction. The research is based on 40 examples of addition, extracted manually from Ukrainian translations of Little Fires Everywhere by Celeste Ng, The Hours by Michael Cunningham, and The Secret History and The Goldfinch by Donna Tartt. All the 40 synesthetic metaphoric descriptions introduced into Ukrainian translations correspond to the source-text non-metaphoric descriptions, though in theory, added synesthetic metaphors could refer to a point in the original where there is no text at all. All of the added synesthetic metaphoric descriptions are based on the TOUCH source domain, which supports Ullmann’s (1957) claim that TOUCH, being the most accessible sensory mode, is a predominant source of cross-sensory transfer. The analysis of results suggests that the translators’ choice to add synesthetic metaphoric descriptions to the target text is influenced by the higher conventionality degree of such descriptions compared to that of the direct non-metaphoric translation equivalents of the non-metaphoric source-text material.
Keywords: addition; conventionality degree; cross-sensory transfer; synesthetic metaphor; translation; GRAC corpus